Modeling of Chronic Myeloid Leukemia: An Overview of In Vivo Murine and Human Xenograft Models - Pallavi Sontakke; Jenny Jaques; Edo Vellenga; Jan Jacob Schuringa (Stem Cells International)
Over the past years, a wide variety of in vivo mouse models have been generated in order to unravel the molecular pathology of Chronic Myeloid Leukemia (CML) and to develop and improve therapeutic approaches. These models range from (conditional) transgenic models, knock-in models, and murine bone marrow retroviral transduction models followed by transplantation. With the advancement of immunodeficient xenograft models, it has become possible to use human stem/progenitor cells for in vivo studies as well as cells directly derived from CML patients. These models not only mimic CML but also have been instrumental in uncovering various fundamental mechanisms of CML disease progression and tyrosine kinase inhibitor (TKI) resistance. With the availability of iPSC technology, it has become feasible to derive, maintain, and expand CML subclones that are at least genetically identical to those in patients. The following review provides an overview of all murine as well as human xenograft models for CML established till date.